Symbiotic Association with Mycoplasma hominis Can Influence Growth Rate, ATP Production, Cytolysis and Inflammatory Response of Trichomonas vaginalis - Margarita, Valentina; Rappelli, Paola; Dessì, Daniele; Pintus, Gianfranco; Hirt, Robert P.; Fiori, Pier L. (Frontiers in Microbiology, 2016)
The symbiosis between the parasitic protist Trichomonas vaginalis and the opportunistic bacterium Mycoplasma hominis is the only one currently described involving two obligate human mucosal symbionts with pathogenic capabilities that can cause independent diseases in the same anatomical site: the lower urogenital tract. Although several aspects of this intriguing microbial partnership have been investigated, many questions on the influence of this symbiosis on the parasite pathobiology still remain unanswered. Here, we examined with in vitro cultures how M. hominis could influence the pathobiology of T. vaginalis by investigating the influence of M. hominis on parasite replication rate, haemolytic activity and ATP production. By comparing isogenic mycoplasma-free T. vaginalis and parasites stably associated with M. hominis we could demonstrate that the latter show a higher replication rate, increased haemolytic activity and are able to produce larger amounts of ATP. In addition, we demonstrated in a T. vaginalis-macrophage co-culture system that M. hominis could modulate an aspect of the innate immuno-response to T. vaginalis infections by influencing the production of nitric oxide (NO) by human macrophages, with the parasite-bacteria symbiosis outcompeting the human cells for the key substrate arginine. These results support a model in which the symbiosis between T. vaginalis and M. hominis influences host-microbes interactions to the benefit of both microbial partners during infections and to the detriment of their host.